2008
DOI: 10.1007/bf03345642
|View full text |Cite
|
Sign up to set email alerts
|

Association of comorbid depression, anxiety, and stress disorders with Type 2 diabetes in Bahrain, a country with a very high prevalence of Type 2 diabetes

Abstract: This study examined the association of depression, anxiety, and stress with Type 2 diabetes (T2DM) in Bahrain, an island-country with a very high prevalence of T2DM. This was a cross-sectional study involving administering Depression Anxiety Stress Scales (DASS)-21 structured depression, anxiety, and stress scale to 143 T2DM patients and 132 healthy controls. Higher proportion of T2DM patients were found in the mild-moderate and severe- extremely severe depression (p=0.002), anxiety (p<0.001), and stress (p<0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
49
4
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 39 publications
12
49
4
6
Order By: Relevance
“…Studies by Islam et al [29] and Saadalla et al [30] independently showed that depression and T2DM are significantly associated. The finding of our study regarding the association of anxiety is also supported by studies conducted by Balhara [8] (P = 0.02), Engum, [7] Almawi et al [31] (P < 0.001), and Afzal et al [32] (OR = 5.348;CI = 2.15-13.29). Stress is also studied as an independent risk factor by various authors like Dutt et al [33] (OR = 4.3;Cl = 2-9.4; P < 0.001), Majgi et al [34] (OR = 10.5; CI = 1.3-90.7, P = 0.03), and Afzal et al [32] (OR = 4.52; CI = 1.95-10.50) and emerged as an independent risk factor for T2DM, which is in concordance with our study.…”
Section: Discussionsupporting
confidence: 89%
“…Studies by Islam et al [29] and Saadalla et al [30] independently showed that depression and T2DM are significantly associated. The finding of our study regarding the association of anxiety is also supported by studies conducted by Balhara [8] (P = 0.02), Engum, [7] Almawi et al [31] (P < 0.001), and Afzal et al [32] (OR = 5.348;CI = 2.15-13.29). Stress is also studied as an independent risk factor by various authors like Dutt et al [33] (OR = 4.3;Cl = 2-9.4; P < 0.001), Majgi et al [34] (OR = 10.5; CI = 1.3-90.7, P = 0.03), and Afzal et al [32] (OR = 4.52; CI = 1.95-10.50) and emerged as an independent risk factor for T2DM, which is in concordance with our study.…”
Section: Discussionsupporting
confidence: 89%
“…Bahrain (2008) (Almawi et al, 2008;Kaur et al, 2013). This may be attributed to inadequate or inefficient coping skills for managing diabetes shortly after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Прослеживается связь между нарастанием уровня стресса и увеличением числа депрессивных расстройств, а также возросшей забо-леваемостью и смертностью от коронарной болезни сердца [6]. Выявлена связь между АГ и депрессией [7]. Именно поэтому в современных условиях про-блема депрессий рассматривается как одна из клю-чевых не только в психиатрии, но и в общей меди-цине [8].…”
Section: Methods and Means Of Anxiety-depression Disorders Correction unclassified
“…Важно отметить тесную коморбидность депрессивных и тревожных рас-стройств. Депрессия почти всегда сопровождается тревожной симптоматикой [7,8].…”
Section: Methods and Means Of Anxiety-depression Disorders Correction unclassified